Respuesta :

Answer:

[tex]f(a) = 2a + 8[/tex]

[tex]f(x + h) = 2x + 2h + 8[/tex]

[tex]\frac{f(x + h) - f(x)}{h} = 2[/tex]

Step-by-step explanation:

Given

[tex]f(x) = 2x + 8[/tex]

Required

[tex]f(a)[/tex]

[tex]f(x + h)[/tex]

[tex]\frac{f(x + h) - f(x)}{h}[/tex]

Solving for f(a)

Substitute a for x in the given parameter

[tex]f(x) = 2x + 8[/tex] becomes

[tex]f(a) = 2a + 8[/tex]

Solving for f(x+h)

Substitute x + h for x in the given parameter

[tex]f(x + h) = 2(x + h) + 8[/tex]

Open Bracket

[tex]f(x + h) = 2x + 2h + 8[/tex]

Solving for [tex]\frac{f(x + h) - f(x)}{h}[/tex]

Substitute 2x + 2h + 8 for f(x + h), 2x + 8 fof f(x)

[tex]\frac{f(x + h) - f(x)}{h}[/tex] becomes

[tex]\frac{2x + 2h + 8 - (2x + 8)}{h}[/tex]

Open Bracket

[tex]\frac{2x + 2h + 8 - 2x - 8}{h}[/tex]

Collect Like Terms

[tex]\frac{2x - 2x+ 2h + 8 - 8}{h}[/tex]

Evaluate the numerator

[tex]\frac{2h}{h}[/tex]

[tex]2[/tex]

Hence;

[tex]\frac{f(x + h) - f(x)}{h} = 2[/tex]